WARISAN ILMIAH MUSLIM & RENAISANS EROPA - Sihaloho, Wardani (UIN Sumatera Utara Medan, 2023)
Renaissance are so important and considered historians as the starting point for the developmentof European civilization. First, European people succeed many achievement in various sector, namely: art, philosophy, literature, science, politics, education, religion, trade and others. Second, Renaissanse has revived the ideals, the realm of thought, the philosophy of life which then structures the standards of the modern world such as optimism, hedonism, naturalism and individualism. Third, the Ancient Greeks and Rome legacies need to revived. Fourth, the incorporation of secular humanism that shifts the human thinking orientation from the theocentric to the anthropocentric. Science had the transmission, dissemination, and proliferation to the Western world that supports the epoch of the Renaissance in Europe. Through the Islamic World, the Western world gained access to deepen and modernized science